Prevalence of Salmonella spp. in environmental samples from table egg barns in Alberta. Issue 6 (2nd November 2017) - St. Amand, Joan A.; Cassis, Rashed; King, Robin K.; Annett Christianson, Colleen B.
ABSTRACT: Some Salmonella spp. are zoonotic, a frequent cause of foodborne illness in Canada, and known to infect humans through contaminated poultry and poultry products. Certain serotypes of Salmonella spp. have been demonstrated to be vertically transmitted from hen to egg. The incidence of Salmonella spp. isolation in the flock has been correlated to its isolation from the environment. Twenty-one producers were enrolled in this study to examine the occurrence of Salmonella spp. in 48 table egg layer flocks housed in 35 barns in Alberta. The purpose of this study was to: (i) identify Salmonella serotypes isolated from the environment of table egg layer facilities in Alberta and (ii) record the prevalence of Salmonella spp. across eight defined environmental sampling points. Salmonella spp. were isolated from the environment of 20/35 barns representing 29/48 flocks. The most common serotypes isolated were S . Heidelberg, S . Kentucky and S . Mbandaka. The order of most to least contaminated sample location was manure belts (54.1%), feeders (47.9%), feed motors (45.8%), egg belts and walls (41.7%), fans (35.0%), cage bottoms (31.3%) and lobbies (27.1%). Salmonella spp. were isolated from 7/7 barns post cleaning and disinfection, demonstrating the persistence of this organism in the environment and the need for effective eradication protocols.